Air-conditioning in modern American architecture, 1890-1970 - Siry, Joseph, 1956- (Buildings, landscapes, and societies, 2021)
"Traces the history of air conditioning as an environmental technology and its integration into American architecture from the turn of the twentieth century to the 1970s"--